Molecular Basis of Taste and Micronutrient Content in Kumamoto Oysters (Crassostrea Sikamea) and Portuguese Oysters (Crassostrea Angulata) From Xiangshan Bay - Liu, Sheng; Xu, Hongqiang; Jian, Shoushuo; Xue, Qinggang; Lin, Zhihua (Frontiers in Physiology, 2021)
Oysters are the most extensively cultivated bivalves globally. Kumamoto oysters, which are sympatric with Portuguese oysters in Xiangshan bay, China, are regarded as particularly tasty. However, the molecular basis of their characteristic taste has not been identified yet. In the present study, the taste and micronutrient content of the two oyster species were compared. Portuguese oysters were larger and had a greater proportion of proteins (48.2 ± 1.6%), but Kumamoto oysters contained significantly more glycogen (21.8 ± 2.1%; p < 0.05). Moisture and lipid content did not differ significantly between the two species (p > 0.05). Kumamoto oysters contained more Ca, Cu, and Zn (p < 0.05); whereas Mg and Fe levels were comparable (p > 0.05). Similarly, there was no significant difference between the two species with respect to total amount of free amino acids, umami and bitterness amino acids, succinic acid (SA), and most flavoring nucleotides (p > 0.05). In contrast, sweetness amino acids were significantly more abundant in Portuguese oysters. Volatile organic compounds profiles of the two species revealed a higher proportion of most aldehydes including (2E,4E)-hepta-2,4-dienal in Kumamoto oysters. Overall, Kumamoto oysters contain abundant glycogen, Ca, Zn, and Cu, as well as volatile organic compounds, especially aldehydes, which may contribute to their special taste. However, free amino acid and flavor nucleotides may not the source of special taste of Kumamoto oyster. These results provide the molecular basis for understanding the characteristic taste of Kumamoto oysters and for utilizing local oyster germplasm resources.